Genomics-based epidemiology of bovine Mycoplasma bovis strains in Israel - Yair, Yael (BMC Genomics, 2020)
BACKGROUND: Mycoplasma bovis is an important etiologic agent of bovine mycoplasmosis affecting cattle production and animal welfare. In the past in Israel, M. bovis has been most frequently associated with bovine respiratory disease (BRD) and was rarely isolated from mastitis. This situation changed in 2008 when M. bovis-associated mastitis emerged in Israel. The aim of this study was to utilize whole genome sequencing to evaluate the molecular epidemiology and genomic diversity of M. bovis mastitis-associated strains and their genetic relatedness to M. bovis strains isolated from BRD in local feedlot calves and those imported to Israel from different European countries and Australia. RESULTS: Phylogeny based on total single nucleotide polymorphism (SNP) analysis of 225 M. bovis genomes clearly showed clustering of isolates on the basis of geographical origin: strains isolated from European countries clustered together and separately from Australian and Chinese isolates, while Israeli isolates were found in the both groups. The dominant genotype was identified among local mastitis-associated M. bovis isolates. This genotype showed a close genomic relatedness to M. bovis strains isolated from calves imported to Israel from Australia, to original Australian M. bovis strains, as well as to strains isolated in China. CONCLUSIONS: This study represents the first comprehensive high-resolution genome-based epidemiological analysis of M. bovis in Israel and illustrates the possible dissemination of the pathogen across the globe by cattle trade.